10-W mid-IR optical parametric oscillators based on ZnGeP2 elements pumped by a fibre-laser-pumped Ho: YAG Laser. Experimental and numerical study. (August 2017) - Antipov, O.L.; Eranov, I.D.; Kositsyn, R.I.
Abstract: The possibility of increasing the power and efficiency of 3.5 – 5.0 μm optical parametric oscillators (OPOs) based on one or two ZnGeP2 crystals pumped by a repetitively pulsed Ho: YAG laser ( λ = 2097 nm), which, in turn, is pumped by a thulium fibre laser ( λ = 1908 nm), is studied. The OPO based on a tandem of ZnGeP2 elements is demonstrated to generate high-quality beams with an average power up to 10 W in pulses with durations of 15 – 25 ns at a repetition rate of ∼17 kHz. The total conversion efficiency of the fibre laser power to the mid-IR radiation reached 25%. A theoretical OPO model explaining a cluster spectrum and higher output power in the case of the ZnGeP2 tandem than in the case of a single element is developed.